2015
DOI: 10.1002/ppp.1836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ground-Based and Helicopter Ground-Penetrating Radar Data Acquired Across an Alpine Rock Glacier

Abstract: To forecast rock glacier movements, it is necessary to have dependable information on their internal structures and physical properties. A first attempt to expand our knowledge of a rock glacier in the Swiss Alps involved acquiring ground-based ground-penetrating radar (GPR) data along numerous profiles using different acquisition systems and antennae with different nominal frequencies. Images derived from these ground-based data were inconsistent and unreliable. For our second attempt, we recorded GPR data us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Additional groundpenetrating radar measurements (GPR) can be applied considering varying frequencies (especially lower ones) to improve the existing data. Similar results related to challenging GPR data were shown by Merz et al (2015) who addressed the high level of noise (especially in areas with low ice contents) to interferences caused by the boulders of the surface layer and shallow heterogeneities; however, they have shown that airborne ground-penetrating radar (antenna mounted on a helicopter) greatly improves the quality of the data. Also other airborne geophysical methods such as frequency-domain or time-domain electromagnetics might help to gain further insights; nevertheless, all airborne methods prefer constant elevation above ground (De Barros and Guimaraes 2016), which can be challenging in alpine terrain.…”
Section: Discussionmentioning
confidence: 57%
“…Additional groundpenetrating radar measurements (GPR) can be applied considering varying frequencies (especially lower ones) to improve the existing data. Similar results related to challenging GPR data were shown by Merz et al (2015) who addressed the high level of noise (especially in areas with low ice contents) to interferences caused by the boulders of the surface layer and shallow heterogeneities; however, they have shown that airborne ground-penetrating radar (antenna mounted on a helicopter) greatly improves the quality of the data. Also other airborne geophysical methods such as frequency-domain or time-domain electromagnetics might help to gain further insights; nevertheless, all airborne methods prefer constant elevation above ground (De Barros and Guimaraes 2016), which can be challenging in alpine terrain.…”
Section: Discussionmentioning
confidence: 57%
“…infiltration of meltwater or degradation of ground ice) (Hilbich et al, 2009;Merz et al, 2015). Their non-invasive nature also allows repeated measurements of the same profile (Hilbich, 2010;Hilbich et al, 2011;Kneisel et al, 2014), which can considerably improve the identification of hydrological processes in alpine permafrost systems Wright et al, 2009), non-permafrost catchments (Kobierska et al, 2015) and in 1-D infiltration studies (Scherler et al, 2010).…”
Section: Geophysical Monitoring and Forward-inverse Modelling Cyclesmentioning
confidence: 99%
“…A reliable interpretation of small-scale geophysical anomalies (or their temporal changes) remains, therefore, difficult (Hilbich et al, 2009). Current challenges for the application of geophysical methods to rock glaciers include (a) the resolution potential for small-scale anomalies and processes (ideally down to the depth of the shear horizon at 15-20 m or more), and (b) the delineation of the complex internal structure and the quantification of the overall ice/water content in a rock glacier (Maurer and Hauck, 2007;Monnier et al, 2011;Monnier and Kinnard, 2013;Hausmann et al, 2007;Merz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ERT is increasingly used in operational permafrost monitoring networks to determine long-term changes in permafrost ice content (Hilbich et al, 2008b(Hilbich et al, , 2011Supper et al, 2014;Doetsch et al, 2015;Pogliotti et al, 2015). Certain geophysical surveys such as Ground-Penetrating Radar (GPR) (Minsley et al, 2015) can also be conducted from airborne platforms (Merz et al, 2015b), enhancing the speed 5 and spatial extent of the measurements.…”
mentioning
confidence: 99%